Sosialisasi Peningkatan Pendapatan Pelaku UMKM Kota Gorontalo - Yahya Antu; Tety Thalib; I Kadek Satria Arsana; Non Endey; Fadly Binolombangan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Importance of UMKM For the development of the region, the village agreed to provide guidance to the community so that they are optimistic about doing business and do not give up easily when faced with failure. . You need to keep your marketing strategy in place. This non-profit service aims to provide the community with the knowledge to increase their income through their MSME business. The method used by this service is socialization. With regards to implementation outcomes, the community understands what is given by resource personnel: innovating and enhancing business leadership to increase profits. Governments can make efforts to facilitate access to capital for implementers of communities, especially MSMEs, and to provide technical guidance for the establishment of new MSMEs within subdistrict governments.